Candida Bloodstream Infections: Changes in Epidemiology and Increase in Drug Resistance. (June 2021) - Kotey, Fleischer CN; Dayie, Nicholas TKD; Tetteh-Uarcoo, Patience B; Donkor, Eric S
The literature on bloodstream infections (BSIs) have predominantly been biased towards bacteria, given their superior clinical significance in comparison with the other types of microorganisms. Fungal pathogens have epidemiologically received relatively less attention, although they constitute an important proportion of BSI aetiologies. In this review, the authors discuss the clinical relevance of fungal BSIs in the context of Candida species, as well as treatment options for the infections, emphasizing the compelling need to develop newer antifungals and strengthen antimicrobial stewardship programmes in the wake of the rapid spread of antifungal resistance.